HELP-SEEKING INTENTION DAN SELF- EFFICACY DALAM MENCARI BANTUAN LAYANAN KESEHATAN MENTAL PADA MAHASISWA - Betta Febryani Sitanggang; Jaka Santosa Sudagijono (EXPERIENTIA : Jurnal Psikologi Indonesia, 2022)
Mental health problems are common among college students. The existence of psychological and social changes that make it difficult for students to adjust during the lecture period can cause individuals become vulnerable for developing mental health problems. Help-seeking early as a protective factor is important to improve students’ mental health and well-being, however most students do not seek professional help when they need to. Self-efficacy can play a role in the formation of help-seeking intention so that it affects individual decisions to seek professional psychological help for their mental health problems. This study aimed to determine the relationship between self-efficacy in seeking mental health care and help-seeking intention among undergraduate students. This research was conducted using purposive sampling on students in East Java aged 18-25 years and had experienced psychological distress. Data were collected using MHSIS (Mental Help-Seeking Intention Scale) and SE-SMHC (Self-Efficacy to Seek Mental Health Care) scale which translated through forward translation dan back translation. The data analysis was performed using Kendall’s Tau-b correlation test. The results showed that self-efficacy in seeking mental health care was positively correlated with help-seeking intention with a correlation coefficient of 0.459 and significance value of 0.000 (p < 0.05), which means the higher self-efficacy (confidence in knowledge and confidence in coping) in seeking mental health care, the higher the student's help-seeking intention. Therefore, students need to maintain healthy relationships with their social networks and expand information about psychological help-seeking.